Investigation on esterified pectin as natural hydrate inhibitor on methane hydrate formation - Effendi, A.D. (Springer Science and Business Media Deutschland GmbH, 2022)
Flow assurance treatment with chemical have become more common as new natural polymers are being develop and are viable for inhibiting hydrate formation in production systems due to its eco-friendly and economical properties. Using high-pressure micro-differential scanning calorimetry (HP-ÂµDSC), the influence of kinetic inhibition on methane gas hydrate formation from synthetic polymer; polycaprolactam (PVCap) and organic polymers (low- and high-methoxylated pectin) was investigated. HP-ÂµDSC was combined with the use of open-ended capillary tubes to counter the stochasticity of hydrate formation which often results in an inconclusive data set without numerous repetitions. By adding the capillary tubes within the cell, more data points on the performance of the inhibitors. Generally, the addition of these inhibitors increased the delay in formation of hydrates compared to the control sample which contained deionized water at 25ËC subcooling and 10Â MPa pressure. However, the two types of organic inhibitors, which are distinguished primarily by the functional group ratios (carboxyl and ester), performed in contrast to one another. The results suggest that the presence of higher carboxyl functional groups is affecting the overall polarity (i.e., low-methoxylated pectin) significantly improved the hydrate inhibition at optimum concentration where both high-methoxylated pectin and PVCap; a commercial inhibitor, performed relatively weaker. In comparison with PVCap, high-methoxylated pectin showed comparable trend and slightly better performances at most concentrations; however, the peak structures indicate discernible difference in the formation mechanism. The use of low-methoxylated pectin at optimum concentration may offer inhibition performance up to three times to that of PVCap at high subcooling. Â© 2022, The Author(s).